Mujeres en cursos de alfabetización en el norte de Marruecos: Un estudio de caso en el círculo rural de Asila - Pérez Beltrán, Carmelo (Studia Orientalia Electronica, 2011)
Illiteracy is one of the main social problems in Morocco. It is even worse among the feminine population of the rural areas, as shown by the census data of 2004. In order to address this problem, some non-formal educational programs have been developed by official institutions and NGOs through development co-operation projects. One of these co-operation projects provides the framework for this research paper, whose main aim is to analyze characteristics of the women who attend alphabetization courses in Asilah’s rural area. Given the data, it can be stated that the general profile of these women is that of an unmarried young woman with no children, who is less than 35 years old with no remunerated job and a limited degree of personal autonomy, but who shows an active interest in formative activities that can contribute to her economic resources.